Istana Seri Menanti, Pekan DiRaja Seri Menanti, Kuala Pilah, Negeri Sembilan [lukisan teknik] - Kh'ng, Ching Fuh; Mhd Hatta Abu Dardak; Puteri Khairul Fathiah Fahimudin; Mohd. Nazri Mahamad Zin; Hazri Abdul Aziz; Hakimi Ahmad (Sekudai : UTM, 1994)
Kajian lukisan terukur (Jabatan Senibina) -- Universiti Teknologi Malaysia, 1994